1983
DOI: 10.1111/j.1471-4159.1983.tb12681.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Enkephalin Activity in Neuroblastoma × Glioma NG108—15 Hybrid Cells by Phospholipases

Abstract: The role of membrane phospholipids in enkephalin receptor-mediated inhibition of adenylate cyclase (EC 4.6.1.1) activity in neuroblastoma X glioma NG108-15 hybrids was studied by selective hydrolysis of lipids with phospholipases. When NG108-15 cells were treated with phospholipase C from Clostridium welchii at 37 degrees C, an enzyme concentration--dependent decrease in adenylate cyclase activity was observed. The basal and prostaglandin E1 (PGE1)-stimulated adenylate cyclase activities were more sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…We also demonstrated that the isolated opiate-binding material contained lipids as well as proteins, and these were apparently critical to its activity. This is consistent with a large and diverse body of evidence indicating that both components are necessary for binding to membrane-bound opiate receptors (18)(19)(20). We now report purification of this material to apparent homogeneity.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…We also demonstrated that the isolated opiate-binding material contained lipids as well as proteins, and these were apparently critical to its activity. This is consistent with a large and diverse body of evidence indicating that both components are necessary for binding to membrane-bound opiate receptors (18)(19)(20). We now report purification of this material to apparent homogeneity.…”
supporting
confidence: 89%
“…As previously reported (17), chromatography of the solubilized brain membranes on Affi-Gel 102 with a linear gradient of NaCl yields two protein peaks. Peak A was eluted at 0.35 M NaCl (fractions [10][11][12][13][14][15][16][17][18][19][20], and peak B at 0.6 M NaCl (fractions [22][23][24][25][26][27][28][29][30][31][32][33][34]. Moreover, the peak A proteins, but not the peak B material, exhibited significant opiate-binding activity.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of opioid receptors to lipids has been well documented. Ligand binding (Lin and Simon, 1978;Abood et al, 1980) and receptor coupling to adenylate cyclase (Law et al, 1983) and low-K, GTPase (Lazar and Medzihradsky, 1990) were inhibited by phospholipase treatment, and unsaturated fatty acids decreased opioid receptor binding in cultured NG 108-15 cells (Ho and Cox, 1982;McGee and Kenimer, 1982). Acidic phospholipids containing polyunsaturated fatty acids enhanced ligand binding to the partially purified p-opioid receptor (Hasegawa et al, 1987), whereas phospholipids inhibited opioid receptor binding in rat brain membranes (Remmers and Medzihradsky, 1987).…”
mentioning
confidence: 99%
“…The cellular response to opiate agonist was determined by measuring either the intracellular cAMP level or the adenylate cyclase activity in membrane preparations as described previously (Law et al, 19833). Intracellular cAMP levels were determined by the method of Schutz and Daly (1973) using [3H]adenine to label the ATP pools.…”
Section: Intracellular Camp and Adenylate Cyclase Quantitationmentioning
confidence: 99%